Age‐associated proteomic alterations in human aortic media. Issue 10 (21st August 2019) - Miura, Yuri; Tsumoto, Hiroki; Iwamoto, Machiko; Yamaguchi, Yuya; Ko, Pojui; Soejima, Yurie; Yoshida, Shoko; Toda, Tosifusa; Arai, Tomio; Hamamatsu, Akihiko; Endo, Tamao; Sawabe, Motoji
Abstract : Aim: Human vascular senescence, which mainly occurs in media, is not completely understood. Here, we used proteomic approaches to investigate age‐associated changes in human aortic media with the goal of understanding the molecular mechanisms underlying vascular senescence. Method: Cryopreserved autopsy samples of aortic media from older‐aged (aged 70–100 years, n = 25), middle‐aged (aged 49–68 years, n = 24), and young (aged 21–39 years, n = 12) subjects were collected. We used two proteomic techniques, two‐dimensional differential gel electrophoresis and isobaric tags for relative and absolute quantitation, and we subjected differentially‐expressed proteins among age groups to immunohistochemical analyses. Results: Proteomic analyses showed that the expression of lactadherin, which produces medin, was elevated in aortic media of older‐aged individuals. Immunohistochemical and Congo red staining showed that lactadherin and apolipoprotein E were deposited, and that amyloidosis was enhanced in older‐aged aortic media. Furthermore, the markers of oxidative damage (8‐hydroxy‐2'‐deoxyguanosine and 4‐hydroxy‐2‐nonenal) were significantly elevated in aortic media of middle‐aged or older‐aged individuals. The immunohistochemical expression of anti‐oxidant proteins (thioredoxin and extracellular superoxide dismutase) was also high in middle‐aged and older‐aged groups. Oxidative damage might induce the disruption of smooth muscle cells, resulting in the decrement of α‐actin, a highly‐expressed protein in smooth muscle cells, and matrix remodeling, in which several proteins associated with extracellular matrix were altered with aging. Conclusions: Proteomic approaches showed that the elevated expression of lactadherin might contribute to amyloid deposition, enhancement of oxidative stress, induction of antioxidant proteins and matrix remodeling in older‐aged aortic media.Geriatr Gerontol Int 2019; 19: 1054–1062 .